PROEM (Revista cientifica In Vestigium Ire, 2016)
With the present volume is has attained consolidate products investigative of authors recognized by your career investigative in which is has attempted perform a review of them recent fields of research in the sciences administrative, accounting and of business.The Division of Administrative Sciences and accounting in line with the teaching activities and projects aimed at the business development of the environment, have put their interest in strengthening five main fields: regional competitiveness and economic development, information and accounting control in private enterprise, regional aspects of the theory of innovation, environmental sustainability, and international business. These fields of research are of base for the structure of the present volume.In the first sections of the volume is can demonstrate investigative work that introduce the reader on the subject of regional competitiveness and economic development with three articles that have one economic, financial and social both Department of Boyaca being travel some of the region’s productive alternatives such as tourism, agriculture and the textile industry.The second part puts as a focus of research innovation. The three articles in this section provide empirical evidence on different aspects of systems of innovation in education, the importance of the economic and social effects with themes as high as domestic violence, economic crimes and the impact of laws on fiscal transparency.The three articles of the third part, are aimed at information and financial control with clear insights for decision making to an international environment and finally presented two articles focusing on sustainability, on the impact of international standards in an important sector in the region such as agriculture, inevitably being topics covered to the same social affectations and the economic environment.Innovation and technological change is considered to often be the basis of competitiveness in the long term. However the innovations induce changes not only in the field economic but also in the processes social and environmental. On the other hand, a region can hardly be considered areas competitive or successful if they are linked in the new business trends, such as also if involve environmental impacts and economic processes that can be sustainable in a society.Satisfied of the bonding of products with a high index investigative, want to invite to the Community administrative, accounting and of business international of the country to add is to this effort national, and in a project very close of character international, toward of improve them publications academic, and so preserve the identity and them reaches that is have defined, for the growth in the collection of contributions and efforts investigative collective.We hope that this space has a participation with progress, proposals, achievements and improvements for journals in the area administrative, accounting and business in the country, and to be able to do so in an atmosphere of support, cooperation and purposeful direction, for the benefit of the social sciences.